Relationship between ownership concentration and financial performance of deposit money banks in Nigeria: Does a turning point exist? / Junaidu Muhammad Kurawa, and Umar Habibu Umar - Kurawa, Junaidu Muhammad; Umar, Umar Habibu (Universiti Teknologi MARA Selangor, 2019)
This study seeks to establish a non-linear relationship between ownership concentration and financial performance of the listed Deposit Money Banks (DMBs) in Nigeria. The data were extracted from the annual reports and accounts of six (6) sampled DMBs from 2003 to 2014. A panel data regression technique was used to analyse the data collected. The study establishes that the relationship between ownership concentration and the financial performance of listed DMBs in Nigeria changes from negative to positive when the ownership concentration reaches 54.94%. This signifies that the relationship between ownership concentration and financial performance is negative if the concentration is below 54.94%. On the other hand, the relationship is positive if it is concentrated above 54.94%. Hence, it is recommended that the ownership of DMBs should not be concentrated below the cut-off point (54.94%) with the view to earning profits.